What does Motivated Mean? Re-Presenting Learning, Technology, and Motivation in Middle Schools via New Ethnographic Writing - Justin Olmanson (Middle Grades Review, 2016)
This article offers a critique of the way middle schoolers are often positioned as generalizable objects that can be acted upon to produce measurable increases in motivation and learning. The critique invites a reconsideration and cultural analysis of some of the dominant discourses and perceptions of technology, young adolescence, and the study of motivation. The use of New Ethnographic Writing—a method that performs a cultural critique via extended scenes connects to the roles and status of motivation, technology, and educational research methods deployed within public schools. Coupled with weak theory, this approach offers a way to understand young adolescents as navigating and wayfaring within complex everyday ecologies that escape notions of developmental level, test scores, motivational indices, and GPA calculations. New Ethnographic Writing and weak theory invite a productive re-orientation to the interactions that take place every day in schools. This invitation comes via a methodological sideways move that draws on non-representational theory and literary non-fiction to form a mode of address that makes relational and momentarily cartographic types of knowing and understanding possible.
Keywords: motivation; technology; science; new ethnographic writing; weak theory; non-representational theory; young adolescence